The physiological function of squalene and its application prospects in animal husbandry - Du, Xin; Ma, Xue; Gao, Yang (Frontiers in Veterinary Science, 2024)
Squalene, which is a natural triterpenoid unsaturated hydrocarbon, is abundant in shark liver and plant seeds. Squalene has various physiological functions such as anti-inflammatory and antioxidant. This paper reviews the physiological functions of squalene and its application prospects in livestock and poultry production, with a view to providing a theoretical basis for its in-depth application in animal husbandry.